A Model of Change of Religious Affiliation - Wallace, Ruth A. (Journal for the scientific study of religion, 1975)
Using a Durkheimian framework this model employs deficiency variables in an attempt to explain change of religious affiliation. All four independent variables (deficit of social rewards, deficit of consistency of life experiences, deficit of religious solidarity, and personal influence) were predicted to be positively related to the dependent variable. Data on 3574 inquirers enrolled in a course of instruction on the tenets of the Roman Catholic Church between 1958 and 1965 were analyzed to test the four major hypotheses. High rates of religious affiliation change occurred among inquirers with two or more deficits who were engaged or married to a Catholic.